مقبوضہ کشمیر میں فکرِ اقبال کی ترویج واشاعت: بشیر احمد نحوی کی علمی وفِکری خدمات: Promotion and Dissemination of Iqbal’s Thought in Occupied Kashmir:The Scholarly and Intellectual Contributions of Bashir Ahmad Nahvi - Hashmi, Dr. Talib Hussain Hashmi (Tashkeel e Jadeed, 2026)
This study examines the promotion and dissemination of Allama Muhammad Iqbal’s thought in Occupied Kashmir with special reference to the scholarly and intellectual contributions of Bashir Ahmad Nahvi. Iqbal’s philosophy of selfhood (Khudi), spiritual awakening, dynamic faith and socio-political consciousness has played a vital role in shaping modern Muslim intellectual discourse. In the specific context of Occupied Kashmir—marked by political uncertainty, cultural challenges and identity struggles the reception and interpretation of Iqbal’s thought acquire deeper significance. Bashir Ahmad Nahvi emerges as a prominent scholar who devoted his intellectual energies to introducing, interpreting, and contextualizing Iqbal’s philosophy for Kashmiri society. Through his research writings, critical essays, lectures and institutional engagement, Nahvi contributed substantially to the growth of Iqbal Studies in the region. His scholarly approach is characterized by clarity of expression, ideological commitment, and contextual relevance, enabling Iqbal’s ideas to resonate with the lived realities of Kashmiri Muslims. The paper highlights how Nahvi not only explained Iqbal’s philosophical concepts but also linked them with issues of cultural identity, moral regeneration, and intellectual resistance. By employing a descriptive and analytical methodology, the study evaluates Nahvi’s major works and academic efforts, demonstrating how his interpretations helped popularize Iqbal’s message among students, researchers, and the educated public of Kashmir.This research argues that Bashir Ahmad Nahvi played a decisive role in transforming Iqbal’s thought from a purely literary-philosophical discourse into a living intellectual force within Kashmiri society. His contributions strengthened the tradition of Iqbal Studies in Occupied Kashmir and ensured the continuity of Iqbal’s intellectual legacy under challenging socio-political conditions. The study ultimately underscores Nahvi’s significance as a mediator between Iqbal’s universal philosophy and the specific Historical and cultural context of Kashmir.